Comparative Effect of Mode of Entry on Undergraduates’ Achievement in Science Education Programs in Federal University of Kashere, Gombe State, Nigeria - Bello, A.; Abdullahi, M.; Ibrahim, I.; Muhammad, I. A. (Kashere Journal of Education, 2021)
This study was carried out to investigate the Effect of Mode of Entry on Undergraduates’ Achievement in Science Education Programs in Federal University of Kashere, Gombe State, Nigeria. The study adopted ex post facto research design in which three research questions guided the study with three corresponding null hypotheses. The DE and UTME science education students who registered in the 2018/2019 academic session were 160 comprising of 72 DE and 88 UTME constituted the sample of the study. Second semester senate approved result of 2018/2019 academic session were used as the base data for analysis. The data was analysed using Mean and Standard deviation to answer the research questions while t-test and ANOVA were used to test the null hypotheses at 0.05 level of significance. Findings revealed a statistically significant difference between the achievement of 200 level DE and UTME in favour of the DE students with medium effect size difference between the achievement of the groups. However, significant difference does not exist between the achievement of 200 level DE and UTME undergraduates admitted in to the seven science education programs. Based on these findings, it was recommended among others that the university management should appeal for the need to change the current DE and UTME admission policy of 40% DE and 60% UTME ratio to 70% DE and 30% UTME respectively. This is to allow the universities to admit the right candidates for the program.